2010
DOI: 10.1128/aem.02350-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Indicators Used in the Development of Predictive Models for Microbial Source Tracking

Abstract: A number of chemical, microbial, and eukaryotic indicators have been proposed as indicators of fecal pollution sources in water bodies. No single one of the indicators tested to date has been able to determine the source of fecal pollution in water. However, the combined use of different indicators has been demonstrated to be the best way of defining predictive models suitable for determining fecal pollution sources. Molecular methods are promising tools that could complement standard microbiological water ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 61 publications
2
46
0
1
Order By: Relevance
“…Laboratory validation of the HPyV and HF183 markers in this study showed the HPyV target to be 100% specific against dog, cattle, and bird fecal samples while the HF183 marker cross-reacted with dog and bird fecal samples and was 81.25% specific to human fecal contamination. Previous studies have reported similar results for both markers (4,18,33). Higher concentrations of HF183 compared to HPyVs in sewage, however, resulted in an M LOD approximately 100-fold lower (more sensitive) for HF183 than for HPyVs in sterile buffered water.…”
Section: Discussionsupporting
confidence: 65%
“…Laboratory validation of the HPyV and HF183 markers in this study showed the HPyV target to be 100% specific against dog, cattle, and bird fecal samples while the HF183 marker cross-reacted with dog and bird fecal samples and was 81.25% specific to human fecal contamination. Previous studies have reported similar results for both markers (4,18,33). Higher concentrations of HF183 compared to HPyVs in sewage, however, resulted in an M LOD approximately 100-fold lower (more sensitive) for HF183 than for HPyVs in sterile buffered water.…”
Section: Discussionsupporting
confidence: 65%
“…It has also been suggested that exposure to sunlight is more detrimental to live cells (as assessed by propidium monoazide treatment) than it is to DNA, implying that the disagreement in the reported literature may be due to the physiological state rather than to a direct effect of sunlight (33). Considerably less is known about the impact of biotic interactions (e.g., predation, competition, and viral lysis); existing laboratory-scale and mesocosm studies suggest that these interactions can play an important role (23,24,26,28), but this assertion has not been confirmed in field studies.…”
mentioning
confidence: 81%
“…Most decay studies to date either have been conducted in the laboratory under simulated environmental conditions or have used closed-microcosm systems (e.g., glass beakers or aquarium tanks) ex situ to mimic ambient conditions (23)(24)(25)(26)(27). Nonetheless, the decay of various Bacteroides host-associated genetic markers has been reported to increase with higher temperatures representative of summer conditions (23,26,28,29), and it appears to be more rapid in freshwater compared to marine waters (25,26,30). The effect of ambient sunlight, however, remains ambiguous.…”
mentioning
confidence: 99%
“…Several studies have reported 100% host specificity of the HF183 marker for non-human fecal samples [51,[66][67][68][69][70]. In contrast, the occasional presence of the HF183 markers in non-human fecal samples has also been reported [52,57,61,71,72], particularly in dog, deer, and chicken feces.…”
Section: Host Specificitymentioning
confidence: 92%
“…Many studies have reported the cross-reactivity of Bacteroides 16S rRNA assays by testing non-human fecal samples [49,[51][52][53][54][55]. The 16S rRNA region is highly conserved between different species of Bacteria and Archaea.…”
Section: Introductionmentioning
confidence: 99%